PENGARUH PERILAKU KEUANGAN, PENGELOLAAN PENAGIHAN PIUTANG TERHADAP PENINGKATAN PENERIMAAN KEUANGAN DI PERUMDA TIRTA MANGKALUKU KOTA PALOPO - Tasya, Aisyah Nurul Tasya (Cakrawala Management Business Journal, 2025)
This research uses quantitative methods and regression analysis to examine how the independent variables of financial behavior and management of receivables collection relate to the dependent variable of company financial revenues. Data was collected through a survey method, where questionnaires were distributed to employees of Perumda Tirta Mangkaluku. Research shows that good financial behavior planning, controlling and recording finances increases financial revenues. In addition, financial receipts increase significantly due to effective management of receivables collection, which includes an organized collection system, monitoring of arrears and appropriate collection strategies. Therefore, the financial stability of a business can be improved with disciplined financial behavior and an effective receivables collection system. This research helps the management of Perumda Tirta Mangkaluku improve its financial strategy and collection system to increase revenue.